Urinary infection related to delayed bladder probe: Bibliographic research (Research, Society and Development, 2021)
This study had as main objective: to point out the factors that influence the emergence of urinary infections after the installation of indwelling vesical catheterization. Bibliographic research, exploratory, descriptive, with a qualitative approach. The survey of articles was carried out in the Virtual Health Library (BVS) and Academic Google, which integrates the following databases: Lilacs, BDENF and Scielo. The following descriptors were used: “Urinary Infection”, “Delayed Vesical Catheterization” and “Nursing”. The period of publication was delimited between the years 2007 to 2018. Data collection took place in April 2020. The analysis of the articles allowed the formulation of 4 thematic categories: length of catheter permanence, high rates of urinary infection in the ICU, conditions aseptic for the procedure and risk factors associated with the installation of urinary infection after indwelling vesical catheterization. The results allowed us to observe that the permanence time of the catheter in the urinary system contributes to the emergence of urinary infection after indwelling urinary catheterization. It was also possible to notice that the rates of urinary infection by this procedure in Intensive Care Units are high and that nurses need, in all hospital scenarios, to be technically-scientifically prepared to carry out this care with the patient in an aseptic and sterile manner. It was concluded that urinary tract infection is an important public health problem today and that it can arise after the indwelling vesical catheterization procedure, requiring the use of correct and aseptic technique for its management.